2019
DOI: 10.3390/su11247239
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Supply Chain Management—A Conceptual Framework and Future Research Perspectives

Abstract: Sustainable operations and sustainable supply chain management (SSCM) have become a highly relevant topic for scientific research and management, as well as policy-making practice. Despite surging growth in extant research, the need for theoretical and conceptual substantiation persists, and large opportunities for further research remain unexploited. This paper responds to the need for a conceptual foundation and, therefore, aims at providing a structured agenda for future research areas in SSCM. Based on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…The emergence of SSCM, which began as a fringe sub-topic of supply chain management [57] can be seen as a response to this stakeholder pressure [2]. The remarkable growth and massive research activity in SSCM attest to the continued academic significance of the topic [3,10,15,[58][59][60], which has also become a seemingly indispensable part of FCs' sustainability activities [2,6,61]. Roy et al [15] take stock of the approaching overwhelming amount of literature on SSCM and develop a thematic landscape schematisation of SSCM research since 2000, in which they prescribe understanding SSCM as a process that begins with adoption, then implementation and extension, and continues with maintenance and then analyses of outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emergence of SSCM, which began as a fringe sub-topic of supply chain management [57] can be seen as a response to this stakeholder pressure [2]. The remarkable growth and massive research activity in SSCM attest to the continued academic significance of the topic [3,10,15,[58][59][60], which has also become a seemingly indispensable part of FCs' sustainability activities [2,6,61]. Roy et al [15] take stock of the approaching overwhelming amount of literature on SSCM and develop a thematic landscape schematisation of SSCM research since 2000, in which they prescribe understanding SSCM as a process that begins with adoption, then implementation and extension, and continues with maintenance and then analyses of outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much has been written on the subject of questionnaire design, with research spanning half a century and continuing into the present (for example: Bradburn et al 2004;Dalal and Hakel 2016;Jenkins and Dillman 2012;Krosnick 2018;Schwarz et al 1991;Tourangeau 1984;Wright and Barnard 1975). In short, respondent's reactions and responses to questionnaires are affected by: the language used, the questionnaire mode, the way the questions are constructed, the self-assessment process that the questionnaire is embedded in and the visual/spatial construction of the questionnaire (Jenkins and Dillman 2012).…”
Section: Challenges In Supplier Self-assessmentmentioning
confidence: 99%
“…In other disciplines much attention has been paid to questionnaires (such as the order of questions, leading vs. open questions etc.) and their design (Bradburn et al 2004;Dalal and Hakel 2016;Jenkins and Dillman 2012;Tourangeau 1984). In our case studies we clearly observed that the ISQ's 'leading questions' (that were noticeably looking for one type of socially desirable response) were overwhelmingly responded to in the expected manner.…”
Section: Main Conclusion On Self-assessment Questionnaires For Sscmmentioning
confidence: 99%
“…The research on social roles in sustainability partner networks has highlighted the role of a lead partner in the chain [40][41][42]. The leader in the chain uses its power to select such suppliers whose sustainability performance is in line with the leader's requirements.…”
Section: Literature Reviewmentioning
confidence: 99%